2018
DOI: 10.1038/s41467-018-04885-3
|View full text |Cite
|
Sign up to set email alerts
|

Formal enantioconvergent substitution of alkyl halides via catalytic asymmetric photoredox radical coupling

Abstract: Classic nucleophilic substitution reactions (SN1 and SN2) are not generally amenable to the enantioselective variants that use simple and racemic alkyl halide electrophiles. The merging of transition metal catalysis and radical chemistry with organometallic nucleophiles is a versatile method for addressing this limitation. Here, we report that visible light-driven catalytic asymmetric photoredox radical coupling can act as a complementary and generic strategy for the enantioconvergent formal substitution of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 48 publications
0
47
0
2
Order By: Relevance
“…α‐Amido alkyl radicals can also be generated by SET oxidation and subsequent decarboxylation with a dicyanopyrazine‐derived chromophore (DZP) as the photocatalyst using α‐amino acids 79 as radical precursors (Figure ) . In combination with α‐bromo ketones as C‐radical precursors, selective cross‐coupling can be achieved.…”
Section: Metal‐free Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…α‐Amido alkyl radicals can also be generated by SET oxidation and subsequent decarboxylation with a dicyanopyrazine‐derived chromophore (DZP) as the photocatalyst using α‐amino acids 79 as radical precursors (Figure ) . In combination with α‐bromo ketones as C‐radical precursors, selective cross‐coupling can be achieved.…”
Section: Metal‐free Processesmentioning
confidence: 99%
“… Asymmetric cross‐coupling of bromoketones 78 with longer‐lived α‐amido alkyl radicals derived from carboxylic acids 79 …”
Section: Metal‐free Processesmentioning
confidence: 99%
“…As in the previous examples, the azaarene nitrogen is proposed to be protonated by the CPA to form chiral ion pair 130, which is then reduced by DPZ •− to give ketyl radical 130 • . The radical 130 • is then reduced further to the carbanion 130 − , which is protonated enantioselectively to give alcohols 131 in excellent yields and enantioselectivities (38 examples, up Jiang et al also reported a series of radical coupling reactions using different CPAs 135a-g and DPZ, with the first examples using α-bromoketones 136 and α-amino acids 137 as radical precursors (Scheme 19a) [66]. The proposed mechanism proceeds through a reductive quenching cycle to generate α-amino radical 137 • and DPZ •− , which can reduce 136 to give α-carbonyl radical 136 • .…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%
“…Die α‐Amidoalkyl‐Radikale können auch durch SET‐Oxidation und anschließende Decarboxylierung mit einem von Dicyanopyrazin abgeleiteten Chromophor (DZP) als Photokatalysator mit α‐Aminosäuren 79 als Radikalvorläufer erzeugt werden (Abbildung ) . In Kombination mit α‐Bromketonen als C‐Radikalvorläufer wurde eine selektive Kreuzkupplung durchgeführt.…”
Section: Metall‐freie Prozesseunclassified
“… Asymmetrische Kreuzkupplung von Bromketonen 78 mit langlebigen von Carbonsäuren 79 abgeleiteten α‐Amidoalkyl‐Radikalen …”
Section: Metall‐freie Prozesseunclassified